Examining Extrinsic Factors that Influence Product Acceptance: A Review. Issue 5 (May 2015) - Li, X.E.; Jervis, S.M.; Drake, M.A.
Abstract Drivers of liking (DOL) studies are useful for product development to formulate acceptable products; however, DOL alone are insufficient for understanding why a product is purchased and repurchased, which is ultimately the indication of a successful product. Ultimately sensory attributes drive product success (that is, repeat and continued purchase). However, ignoring the importance of extrinsic factors may neglect the vital product attributes responsible for the initial purchase, which may in turn, affect repeat purchase. The perception of sensory attributes assessed by DOL is mitigated by external perceptions of quality. If the sensory attributes do not deliver based upon the quality cues, the product will not be acceptable. Four key extrinsic factors that affect DOL are the perceived satiety, brand and labeling, price, and the emotional impact to decision making. In order to more thoroughly understand what the DOL for a product is, these 4 product cues should be considered in conjunction with sensory attribute perception to gain a holistic understanding of product acceptance.